PERILAKU PENGELOLAAN KEUANGAN: PENDAPATAN, SIKAP KEUANGAN, LITERASI KEUANGAN, DAN LOCUS OF CONTROL SEBAGAI VARIABEL INTERVENING - Desi Ariyani Romadoni; Yuyun Ristianawati (ITB AAS Indonesia Surakarta, 2024)
The purpose of this research is to determine the influence of income, financial attitudes and financial literacy on financial management behavior through locus of control as an intervening variable in Semarang Regency MSMEs. The research method used is quantitative research. The sampling technique used was purposive sampling of 100 MSME respondents in the Semarang Regency area. The data used in this research is primary data by distributing questionnaires to MSMEs. The questionnaire consists of the respondent's identity as well as statements related to financial management behavior. Data were analyzed using SPSS version 25 software by testing validity, reliability, classical assumptions, multiple regression, coefficient of determination, and Sobel test. The results of this research show that income and financial literacy have a positive and significant effect on locus of control in MSMEs; financial attitude does not have a positive and significant effect on locus of control in MSMEs; there is a positive and significant influence between income, financial literacy, and locus of control on financial management behavior in MSMEs; and there is no positive and significant influence of financial attitudes on financial management behavior in MSMEs; income and financial attitudes mediated by locus of control have no effect on financial management behavior; Financial literacy mediated by locus of control influences financial management behavior.